The Influence of Shopee Promotions on The Purchase Interest of Students at The Faculty of Economics and Business, Widya Dharma University Pontianak - Wong, Leon; Juvian Khowira, Mario; Robert; Patricia, Verent; Bondan, Vinsensius; Effendy, Dudy (Journal of Nusantara Economic Science, 2024)
This study was conducted to test the effect of Shopee promotions on the purchasing interest of students at the Faculty of Economics and Business, Widya Dharma University, Pontianak, considering the importance of promotions in driving purchasing decisions in the current digital shopping era. Shopee, one of the e-commerce in Indonesia, often uses various promotional strategies such as discounts, cashback, flash sales and free shipping vouchers to attract the attention of consumers, especially the younger generation such as students. The population of this study were students at the Faculty of Economics and Business, Widya Dharma University, Pontianak, with a research sample of 50 individuals. The data collection method in this study was a survey method with Google Form used as a medium for distributing questionnaires. Data quality testing used validity and reliability tests. As for data analysis, researchers used the Pearson correlation test, simple regression analysis, and determination tests. The results of the study showed that there was an influence between the Independent variable (Promotion) carried out by Shopee on the Dependent Variable (Buying Interest) of Students at the Faculty of Economics and Business, Widya Dharma University, Pontianak.